صعوبات الدرس البلاغي لدى الناطقين بغير العربية(الترجمة من العربية إلى الملايويةأنموذجا) - Elsayed Mohamed Salem, Salem Elawadi (2020)
Undoubtedly the flag of rhetoric rests on a group Examples and evidence that are shown by their explanation are the second meanings Underlying the first meanings of expression, This requires that the eloquent scholar be familiar in the first sense of the pretense of words, and then look for the hidden meanings of the author. The problem of research lies in the difficulty of the rhetorical lesson of non-Arabic speakers. They must first master language skills and control the first meanings so that they can access the second meanings that are essentially the subject of the rhetorical lesson. In addition, the Arabic language teacher often translates these examples into the language of the learner; if the teacher is not familiar with the source language and understands it and interprets its mother language, he cannot communicate the meaning of those examples. Those who do not master the translation go astray and mislead others. In this research, we have proved the problem of translating the language of the Qur'an in general because most of the examples of the Qur'an are derived from the Qur'an, and we have mentioned the causes of the problem of translating the Qur'an. Then we followed that with the problems of translating the analogy, metaphor and simile. We supported what we mentioned with examples of difficulty The Malay reader to translate the Arabic rhetorical. The result is that Arabic rhetoric is translated into language Malay is varied and makes it very difficult for students who non speak arabic to understand the lesson Rhetorical. The translator must therefore explain this to the Malay reader. Finally, the research provided some solutions to that problem.